Analysis of multifinger power HEMTs supported by effective 3-D device electrothermal simulation. (November 2017) - Chvála, Aleš; Marek, Juraj; Príbytný, Patrik; Šatka, Alexander; Stoffels, Steve; Posthuma, Niels; Decoutere, Stefaan; Donoval, Daniel
Abstract: The influence of the metallization layer geometry on the electrothermal behavior of the multifinger power high-electron mobility transistors (HEMTs) is studied. The analysis of thermal and electrical behavior is supported by effective 3-D electrothermal device simulation method developed for Synopsys TCAD Sentaurus environment using mixed-mode setup. The proposed methodology allows fast simulation of complex systems from individual semiconductor layers at a frontend up to package and cooling assemblies at a backend. More accurate electrothermal model of power HEMT is proposed and validated by finite element method (FEM) simulations. The analysis points on significant influence of metallization geometry design on electrothermal properties and reliability of the multifinger power HEMTs. The unique identification and visualization of the critical regions allows effective device optimization. Very good comparison between simulation results and experimental data demonstrate validity of the proposed simulation methodology and HEMT structures analysis.